Rekonstruksi Makna Jihad: Studi Kasus Terorisme di Indonesia - Ananda Emiel Kamala (Universitas Nahdlatul Ulama Blitar, 2022)
Jihad and terrorism are two words that cannot be separated between the two. Phenomena associated with acts of terrorism are often misinterpreted by calling them acts of jihad, even jihad is often used as a justification in carrying out various movements that lead to religious radicalism. This study aims to uncover and reconstruct the meaning of jihad which has been misinterpreted by some elements in understanding it. Those who consider acts of terrorism as a form of jihad, especially jihad in religion, are based on lack of accuracy in understanding the contents contained in the verses of al-Qur'an, Hadith or al-Kitab, so the ideology that is born will also be different. This inaccurate ideology should be able to be changed and rectified by reviewing the verses of the Qur'an, the Hadith, and the Scriptures relating to jihad. The lack of insight held by the general public in understanding the meaning of jihad is one of the triggers for being easily influenced by actions that lead to terrorism. The role of religion and the state seems to be demanded extra in tackling various problems related to suicide bombings which are considered as a form of jihad by some elements. It is necessary to place heavy emphasis and legal action on those who misuse the meaning of jihad as an act of terrorism in the interests of certain groups. These actions must be eradicated to the root and embryo